Hipertensão arterial sistêmica: fatores de risco em quilombolas - PEREIRA, Joelmara Furtado dos Santos (2019)
Systemic Arterial Hypertension is understood as one of the great public health problems in Brazil and around the world. Seen as the main cause of preventable deaths in developing countries, it appears among the most prevalent diseases in non-white colored individuals and is associated with lower social groups, emphasizing the special conditions of vulnerability experienced by the black population. This study aimed to assess the risk factors for Systemic Arterial Hypertension in slave descendants (quilombolas). This is a cross-sectional study, descriptive-analytical, which was conducted with the quilombola community of Santana dos Pretos from August 2018 to February 2019. The research had the participation of 177 quilombolas aged 18 or over. In order to collect data, we used a validated form, adapted to the reality of the community, based on the National Health Survey and on the electronic form of the Vigitel system. We performed anthropometric screening and blood pressure measurement. The data were analyzed using the IBM SPSS Statistics 20 (2011) program by adopting a significance level of 5% (p<0.05). Systemic Arterial Hypertension showed a prevalence of 22.2%. The community is mostly composed by people who self-declare black skin color, women, young, farmers and with a monthly family income up to a minimum wage, all of them living in rural areas. As for risk factors, we identified: age (>= 60 years; p<0.030), BMI obesity (p<0.001), greatly increased waist circumference (p<0,010), physical inactivity (p<0,043) and the irregular consumption of vegetables (p<0,041). We concluded that the risk factors were present in the interviewees and that Systemic Arterial Hypertension had prevalence similar to the findings of national studies, but diverging from studies involving quilombolas.